2019
DOI: 10.1111/joor.12903
|View full text |Cite
|
Sign up to set email alerts
|

The association between oral bacteria, the cough reflex and pneumonia in patients with acute stroke and suspected dysphagia

Abstract: Objective: To establish how oral bacteria are related to cough sensitivity and pneumonia in a clinical stroke population.Background: Stroke patients are at risk of colonisation by respiratory pathogens due, in part, to sudden discontinuation of effective oral hygiene. When combined with reduced cough reflex sensitivity, aspiration of contaminated oropharyngeal contents and can lead to pneumonia. Relationships between oral bacteria, cough sensitivity and pneumonia have not been established. Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Consequently, a higher prevalence of P. aeruginosa and Enterobacteriaceae (other GNB) was seen in severe ACAP patients. As the oral cavity is considered the principal source of pathogens responsible for aspiration pneumonia, our results suggest a shift in the oral flora of severe ACAP patients (12,40,41).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Consequently, a higher prevalence of P. aeruginosa and Enterobacteriaceae (other GNB) was seen in severe ACAP patients. As the oral cavity is considered the principal source of pathogens responsible for aspiration pneumonia, our results suggest a shift in the oral flora of severe ACAP patients (12,40,41).…”
Section: Discussionmentioning
confidence: 70%
“…Microbiology data from patients with other comorbid conditions suggested that P. aeruginosa, K. pneumoniae, and E. coli were frequently isolated from oral samples (40,42). These results should alert clinicians of the need to appropriately cover against GNB in severe ACAP, especially if risk factors for pseudomonas are present.…”
Section: Discussionmentioning
confidence: 84%
“…Poor oral health in combination with dysphagia has been identified in particular in stroke and geriatric patients as a risk factor for aspiration pneumonia [ 206 , 207 ]. In addition to periodontitis, gingivitis, plaque formation and caries, respiratory pathogens such as Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Klebsiella oxytoca, Pseudomonas aeruginosa and Escherichia coli have frequently been detected in the oral cavity of these patients [ 208 ].…”
Section: Therapymentioning
confidence: 99%
“…The study also demonstrated that the change in bacteria levels is associated with the development of pneumonia. The researchers concluded that the presence of respiratory flora in patients’ mouths within 48 hours of a stroke is clinically significant [ 36 ].…”
Section: Reviewmentioning
confidence: 99%